Investigation of Electromagnetic Shielding Performance of Monolayer Ironboride in Tetragonal Crystal Structure using Ab initio Methods - İzzet Paruğ Duru; Hakan Üşenti (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The negative effects of pollution caused by electromagnetic radiation on human health and sensitive systems have reached serious dimensions. The most effective way to deal with this pollution is to create isolated areas with shielding materials. Especially after the discovery of graphene, studies on 2D materials continue to reveal the extraordinary structural, electronic and optical properties of 2D materials. Thanks to the research on the use of monolayer materials in electromagnetic shielding, ultra-thin and high-performance shielding materials are being obtained. In this study, the electromagnetic radiation shielding efficiency (SE) of a 2D film-structured material with a tetragonal crystal structure in the MBene class of the MXene family and obtained using Fe2B unit cells in the P4/mmm space group has been investigated using ab-initio methods. The electrical, optic and magnetic behavior of the material in the ground state is determined using the density functional theory (DFT) approach. The Curie temperature was investigated using the Monte Carlo method. The shielding efficiency of Fe2B has been investigated in the range of 31.558-123980 nm of the electromagnetic wave spectrum at [001], [010], [100] polarization states. Despite Fe2B 2D monolayer film structure, it showed a shielding performance (SET) of gt;20 dB. This study shows that Fe2B in film structure is a promising and exciting material for ultra-thin shielding material applications with its superior shielding performance at nanometer dimensions.